PSYCHOLINGUISTIK ASPECTS OF COLOR PERSEPTION AND LANGUAGES - H.Urakova (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation. This article examines the psycholinguistic mechanisms underlying the perception of colors and their representation in language. It explores how cognitive processes, cultural background, and linguistic structures influence the interpretation and categorization of color terms. The study draws on findings from psycholinguistics, cognitive linguistics, and cross-cultural research, highlighting the interaction between perceptual experience and linguistic expression. The results show that human color perception is not only biologically universal but also shaped by language-specific categories, cultural symbolism, and individual cognition.